Development and psychometric properties of a questionnaire to assess the female quality of sexual life - Raziyeh Maasoumi; Morteza Nazifi; Zahra Mokhtarinia; Lorann Stallones (Nursing Practice Today, 2020)
Background & Aim: Proper assessment of the quality of sexual life requires having access to psychometrically sound instruments. The present study aimed to develop an instrument to assess Iranian women’s quality of sexual life.